Body mass index, functional fitness and nutritional behaviours of senior women from the Kraków population - Maria Gacek; Agnieszka Wojtowicz; Grażyna Kosiba; Magdalena Majer; Joanna Gradek (National Institute of Public Health - National Institute of Hygiene, 2023)
Background. Body Mass Index (BMI) is dependent on, among others, diet and level of physical activity. Seniors are more prone to nutritional disorders than other population groups. Objective. The aim of the study was to analyse the relationship between BMI and nutritional behaviours as well as the functional fitness level of senior women. Materials and methods. The research was carried out among a group of 120 women aged 60-84, using the TANITA SC-330ST body composition analyser, the HOLTAIN anthropometer, the Fullerton Functional Fitness Test and the authordesigned nutritional behaviour questionnaire for seniors. Statistical analyses were conducted using the IBM SPSS 21 statistical package, applying the Kruskal-Wallis ANOVA tests with comparisons of z tests at the significance level p<0.05. Results. In terms of the relationship between BMI and functional fitness indices, it was shown that women with normal weight obtained higher results for the lower body (p=0.043) and upper body agility tests than obese women (p<0.001). Females with normal BMI also obtained higher results in the endurance test than the overweight women (p=0.038). In terms of the correlation between BMI and nutritional behaviours, it was demonstrated that women with a healthy body mass more often ate varied, low-volume meals than those overweight (p=0.026). Women with correct weight ate fish, eggs and lean meat more often than obese women (p=0.036). Obese women consumed 3-5 portions of fruit and vegetables less frequently during the day than women with normal body mass (p=0.029) and those overweight (p=0.015). Obese women were less likely to eat sea fish at least 1-2 times a week than overweight females (p=0.040) and those with normal BMI (p<0.001). At the same time, women with a normal BMI indicated a higher degree of performed daily physical activity than the overweight women (p=0.028) and those with obesity (p=0.030). Conclusions. Women with normal BMI presented more rational nutrition habits and higher functional fitness than overweight and obese senior women.